People's Republic of China : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1996)
This Selected Issues paper examines the decline in the revenue-to-GDP ratio for the People's Republic of China. In common with most transition countries, China has experienced a sharp decline in fiscal revenues since the initiation of economic reforms, owing mainly to weakness in tax revenues. This paper describes the secular decline in the revenue ratio in China and reviews the factors behind the decline. It also compares China's experience with that of other transition countries where revenues have tended to decline.